2009
DOI: 10.1021/nl803487r
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Surface Charges in Cellular Adsorption versus Internalization by Selectively Removing Gold Nanoparticles on the Cell Surface with a I2/KI Etchant

Abstract: This Letter presents a new method for differentiating the Au nanospheres attached to the cell surface from those being internalized into the cells. We introduced an etching solution based on I2 and KI that can selectively dissolve the Au nanospheres on the cell surface within a short period of time. The advantage of this etchant is its low toxicity to the cells because it is capable of etching away a relatively large amount of Au nanospheres at a low molar concentration. By combining with quantitative elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
655
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 749 publications
(703 citation statements)
references
References 42 publications
27
655
0
4
Order By: Relevance
“…2,18,32,[44][45] Several researches have been conducted to probe GNPs-cell interactions in the past few years. It has been reported that the sign of surface charges can dramatically influence uptake of GNPs.…”
Section: The Influence Of Physiochemical Properties To Biological Effmentioning
confidence: 99%
“…2,18,32,[44][45] Several researches have been conducted to probe GNPs-cell interactions in the past few years. It has been reported that the sign of surface charges can dramatically influence uptake of GNPs.…”
Section: The Influence Of Physiochemical Properties To Biological Effmentioning
confidence: 99%
“…8,9 Previous studies have shown that the uptake of NPs by living cells is affected by NP properties such as size [10][11][12][13] and surface. [14][15][16] However, NPs dispersed in a biological fluid are rapidly covered by biomolecules, such as proteins and lipids, forming a biomolecular 'corona' that effectively screens the bare NP surface. [17][18][19][20][21][22] When cells are exposed to NPs it is therefore, in realistic circumstances, typically not the bare NP surface that interacts with the cell but the NP-biomolecular corona complex.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated this aspect, for example by exposing cells to NPs at 4 °C to inhibit internalisation [30][31][32] , or by dissolving NPs on the outside of the membrane. 15 Information on NP adhesion to membranes composed solely of lipids is also emerging by studying their adsorption onto micron-sized particles coated with lipids. 33 In this work we have investigated the adhesion properties of NPs with a particular emphasis on the effect of the biomolecular corona.…”
Section: Introductionmentioning
confidence: 99%
“…Uptake of nanoparticles is thought-as agreed upon by a majority of the research community-to be realized via the energy-dependent biological process of endocytosis, in addition to passive diffusion and mechanical or biochemical damage in the lipid membrane induced by the trespassing nanoparticle. 1 However, despite intensive research efforts, both experimentally [11][12][13][14][15][16][17][18][19][20] and through atomistic and coarsegrained computer simulations, [21][22][23][24][25] it remains unclear and often controversial as to what extent the thermodynamic and endocytotic pathways may individually contribute to the convoluted process of nanoparticle cell uptake.…”
mentioning
confidence: 99%